2013
DOI: 10.17660/actahortic.2013.974.10
|View full text |Cite
|
Sign up to set email alerts
|

Weevil Resistant Sweetpotato Through Biotechnology

Abstract: Weevils damage about a quarter of the sweetpotato harvest in Uganda and induce the accumulation of toxic compounds in the healthy-looking parts of damaged storage roots. We have introduced new genes that produce anti-weevil proteins in the sweetpotato storage root through biotechnology. We may have found few with some resistance to weevils. In parallel, we are testing a new strategy to weaken specific genes of the weevils to block their development. These two strategies will eventually be combined into widely-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Since insecticidal proteins tend to be moderately host specific, the first step in working towards a transgenic plant is to identify proteins active against SPW (Rukarwa et al 2013). Several proteins have been identified as toxic to SPW and it has been demonstrated that they could be used independently (Hernández-Martínez et al 2020;Prentice et al 2011). Although transgenic approaches are a routine and widely used component of other crop systems for insect control, similar to the case with a gene suppression strategy, it remains at an early stage for sweetpotato as effective SPW protein toxins or their requisite transgene expression is limiting (Morán et al 1998;Hernández-Martínez et al 2020).…”
Section: Transgenic Plantsmentioning
confidence: 99%
“…Since insecticidal proteins tend to be moderately host specific, the first step in working towards a transgenic plant is to identify proteins active against SPW (Rukarwa et al 2013). Several proteins have been identified as toxic to SPW and it has been demonstrated that they could be used independently (Hernández-Martínez et al 2020;Prentice et al 2011). Although transgenic approaches are a routine and widely used component of other crop systems for insect control, similar to the case with a gene suppression strategy, it remains at an early stage for sweetpotato as effective SPW protein toxins or their requisite transgene expression is limiting (Morán et al 1998;Hernández-Martínez et al 2020).…”
Section: Transgenic Plantsmentioning
confidence: 99%
“…Therefore, Bt sweetpotato varieties expressing these Cry proteins might be protected against weevils. To that end, the corresponding genes were introduced into sweetpotato via Agrobacterium tumefaciens genetic transformation (Ghislain et al 2013 ). Assuming weevil pests will be controlled through the expression of the Cry proteins in sweetpotato, it is important to assess the impact of these proteins on other organisms in the sweetpotato growing environments, like other insect control technologies.…”
Section: Weevil-resistant (Bt) Sweetpotato For Ugandamentioning
confidence: 99%